Acquired angioedema in B cell lymphoproliferative disease: A retrospective case series. (11th October 2021) - Wonnaparhown, Alex; Stefanovic, Alexandra; Lugar, Patricia; Hostetler, Haley P
Abstract: Acquired angioedema due to C1-inhibitor (C1-INH) deficiency (AAE-C1-INH) is rare and is associated with underlying lymphoproliferative diseases. C1-INH deficiency may be due to neoplastic over-consumption of C1-INH and the generation of anti-C1-INH autoantibodies. Uncovering an occult malignancy can lead to earlier oncology referral and improvement of angioedema after treatment of the underlying lymphoproliferative disorder. We characterized seven patients with C1-INH-AAE that highlights the importance of recognizing the association between C1-INH-AAE and underlying malignancy. In acute attacks, patients may be resistant to C1-INH therapy due to the presence of anti-C1-INH autoantibodies or rapid complement consumption, and may respond better to icatibant or ecallantide, which directly affect bradykinin. Treatment of the underlying malignancy also improves AAE-C1-INH symptoms and supports the role of lymphoproliferative B cells in AAE-C1-INH pathophysiology. Monitoring levels of C4, C1-INH function and level, and C1q may be predictive of AAE-C1-INH control and be used as surrogates for treatment efficacy. With close monitoring, low-dose danazol can be effective for long-term prophylaxis. Annual evaluation in AAE-C1-INH is recommended if an underlying malignancy is not found, as angioedema may precede the development of malignancy by several years. Our single-center study has aided in standardization of comprehensive AAE-C1-INH diagnosis, treatment, and monitoring strategies towards future therapeutic clinical trials.